ANALYSIS OF THE EFFECTIVENESS OF LEADING SECTOR IMPLEMENTATION IN MAJELIS DAERAH KEDIRI UTARA I - Akde Triyoga (Pedagogic Research-Applied Literacy Journal, 2026)
This study aims to evaluate the effectiveness of the Leading Sector program using the CIPP evaluation model (Context, Input, Process, Product). The Leading Sector is a program strategy in which selected congregations with certain potential act as the main implementers, while the District Council (Majelis Daerah) serves as the coordinator. This research employed a quantitative approach with explanatory research design. Data was collected through questionnaires from 93 respondents consisting of PHMJ, BPMJ, and organizing committees from four congregations that had implemented the Leading Sector. Multiple linear regression analysis was applied to examine the influence of context, input, and process variables on product. The findings revealed that context, input, and process significantly influenced the product, contributing 51.4% (R² = 0.514). Among these, process was found to be the most dominant factor affecting program success. In general, respondents assessed the aspects of context, input, process, and product as being in the “fair” category. However, improvements are still needed in terms of clarifying program objectives, ensuring equitable funding, strengthening coordination, and encouraging innovation in implementation. In conclusion, the Leading Sector program is considered sufficiently effective and feasible to continue, with necessary improvements particularly in the areas of socialization, funding, and coordination between the District Council and implementing congregations.